Willa Cather's Pittsburgh - Bintrim, Timothy W.; Jaap, James A.; Vanderlaan, Kim (Cather studies, 2021)
"Cather Studies, Volume 13 explores the myriad ways that Willa Cather's writing career was shaped during the crucial years in Pittsburgh and the artistic, professional, and personal connections she made there"--